2014
DOI: 10.1111/cbdd.12477
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Design and Synthesis of a Small Molecule that Exhibits Anti‐inflammatory Activity by Inhibition of MyD88‐mediated Signaling to Bacterial Toxin Exposure

Abstract: Both Gram-positive and Gram-negative pathogens or pathogen-derived components, such as staphylococcal enterotoxins (SEs) and endotoxin (LPS) exposure, activate MyD88-mediated pro-inflammatory cellular immunity for host defense. However, dysregulated MyD88-mediated signaling triggers exaggerated immune response that often leads to toxic shock and death. Previously, we reported a small molecule compound 1 mimicking BB-loop structure of MyD88 was capable of inhibiting pro-inflammatory response to SEB exposure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Compounds 4 – 56 were tested for inhibition of cytokines in primary human peripheral blood mononuclear cells (hPBMCs) treated with F. tularensis LPS extracts (10 μg/ml) using an adaptation of protocols previously described for other pathogens . Cells were preincubated with test compound for 30 min and then exposed to LPS extracts from F. tularensis (10 μg/ml) for 16 hr.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Compounds 4 – 56 were tested for inhibition of cytokines in primary human peripheral blood mononuclear cells (hPBMCs) treated with F. tularensis LPS extracts (10 μg/ml) using an adaptation of protocols previously described for other pathogens . Cells were preincubated with test compound for 30 min and then exposed to LPS extracts from F. tularensis (10 μg/ml) for 16 hr.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were preincubated with test compound for 30 min and then exposed to LPS extracts from F. tularensis (10 μg/ml) for 16 hr. Cytokine response was measured using a MSD human proinflammatory fourplex ultrasensitive kit (TNF‐α, IFN‐γ, IL‐6, IL‐1β) with electrochemiluminescent output . The calibrated response curve demonstrated that all four cytokines gave a linear response in the range of 1 pg/ml to 10 μg/ml of LPS extracts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations